GAMBARAN POLA MAKAN IBU HAMIL DI KLINIK YOSTVAN SIDOARJO - Setiawan Putri, Erni (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2023)
Diverse and varied dietary patterns will meet the nutritional needs of the mother and fetus. Unhealthy eating patterns result in a fetus lacking nutrition, this is often associated with the incidence of complications and disability in infants. In the preliminary survey conducted by researchers found 10 first trimester pregnant women who still complained of nausea and vomiting. This study aimed to determine diet in pregnant women at Yostavan Clinic, Sidoarjo. The method used was descriptive. The independent variable in this study was a description of eating patterns and the dependent variables were pregnant women, the sampling technique used was consecutive sampling with the selection of subjects who met the inclusion criteria in the period March-April 2019 to 36 respondents. The instrument used was the SQ-FFQ (Semi-Quantitative Food Frequency Questionnaire) questionnaire which was filled in by respondents for 3 days. Percentage descriptive statistical analysis yielded 33% had a balanced diet and 67% havent unbalanced diet